2005
DOI: 10.1097/01.ss.0000185906.18460.65
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Natural Radionuclides and Selected Major and Trace Elements Along a Soil Toposequence in the Central Spanish Pyrenees

Abstract: Natural gamma-emitting radionuclides ( 238 U, 226 Ra, 232 Th, 210 Pb) and selected major and trace elements (Ca, K, Mg, Na, Fe, Al, Mn, Pb, Ba, Zn, Sr, Li, Co, Ni, Cu, Cr, Cd) were determined in a soil toposequence along a mountain slope of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 24 publications
6
23
0
Order By: Relevance
“…The background levels of natural gamma radionuclides fell within the range of values observed in the region and elsewhere in Spain (Navas et al, 2002b(Navas et al, , 2005a and were similar to those reported by Litaor (1995) andde Jong et al (1994) in North America and by Fujiyoshi & Sawamura (2004) in Germany.…”
Section: Factors Affecting the Distribution Of The Radionuclidessupporting
confidence: 69%
See 2 more Smart Citations
“…The background levels of natural gamma radionuclides fell within the range of values observed in the region and elsewhere in Spain (Navas et al, 2002b(Navas et al, , 2005a and were similar to those reported by Litaor (1995) andde Jong et al (1994) in North America and by Fujiyoshi & Sawamura (2004) in Germany.…”
Section: Factors Affecting the Distribution Of The Radionuclidessupporting
confidence: 69%
“…Furthermore, in the forest side of the catchment where carbonate content and pH were low, leaching was favoured especially in rich organic soils and, consequently, 11 some clays have accumulated in the deepest layers (Navas et al, 2005a). However this is not observed at the shrub side where carbonates are abundant.…”
Section: Factors Affecting the Distribution Of The Radionuclidesmentioning
confidence: 89%
See 1 more Smart Citation
“…For sludge samples from rice fields, the data obtained were in agreement with those reported by Navas et al (2005) for cultivated soil from Spain's Pyrenees Mountains (1.6-8.4 Bq/kg). The high dispersion of these values is due to the remobilisation and homogenisation of the cultivated soils.…”
Section: Impact Of Industries In the Accumulation Of Radionuclidessupporting
confidence: 81%
“…This is, in part, due to the fact that 210 Po is very insoluble in water (Tanaka et al, 1983), therefore the majority of 210 Po in the water column is bound to suspended particulate material. Moreover, 210 Po is very strongly adsorbed by Fe(OH) 3 in the soil so the concentration in water is negligible (Wanty et al, 1991;Navas et al, 2005). 230 Th is also very insoluble in water so its activity in water is negligible.…”
Section: Regression Analysis Of the Radionuclidesmentioning
confidence: 99%